Combined VEGF and PD-L1 blockade displays synergistic treatment effects in an autochthonous mouse model of small cell lung cancer - Meder, Lydia; Schuldt, Philipp; Thelen, Martin; Schmitt, Anna; Dietlein, Felix; Klein, Sebastian; Borchmann, Sven; Wennhold, Kerstin; Vlasic, Ignacija; Oberbeck, Sebastian; Riedel, Richard; Florin, Alexandra; et al. (Cancer Research, 2018)
Small cell lung cancer (SCLC) represents the most aggressive pulmonary neoplasm and is often diagnosed at late stage with limited survival, despite combined chemotherapies. We show in an autochthonous mouse model of SCLC that combined anti-VEGF/anti-PD-L1-targeted therapy synergistically improves treatment outcome compared with anti-PD-L1 and anti-VEGF monotherapy. Mice treated with anti-PD-L1 alone relapsed after 3 weeks and were associated with a tumorassociated PD-1/TIM-3 double-positive exhausted T-cell phenotype. This exhausted T-cell phenotype upon PD-L1 blockade was abrogated by the addition of anti-VEGF-targeted treatment. We confirmed a similar TIM-3-positive T-cell phenotype in peripheral blood mononuclear cells of patients with SCLC with adaptive resistance to anti-PD-1 treatment. Mechanistically, we show that VEGFA enhances coexpression of the inhibitory receptor TIM-3 on T cells, indicating an immunosuppressive function of VEGF in patients with SCLC during anti-PD-1-targeted treatment. Our data strongly suggest that a combination of anti-VEGF and anti-PD-L1 therapies can be an effective treatment strategy in patients with SCLC.
CRIS-Team Scopus Importer:2023-03-21